Optical Control of Mitosis with a Photoswitchable Eg5 Inhibitor. Issue 9 (14th January 2022) - Impastato, Anna C.; Shemet, Andrej; Vepřek, Nynke A.; Saper, Gadiel; Hess, Henry; Rao, Lu; Gennerich, Arne; Trauner, Dirk
Abstract: Eg5 is a kinesin motor protein that is responsible for bipolar spindle formation and plays a crucial role during mitosis. Loss of Eg5 function leads to the formation of monopolar spindles, followed by mitotic arrest, and subsequent cell death. Several cell‐permeable small molecules have been reported to inhibit Eg5 and some have been evaluated as anticancer agents. We now describe the design, synthesis, and biological evaluation of photoswitchable variants with five different pharmacophores. Our lead compound Azo‐EMD is a cell permeable azobenzene that inhibits Eg5 more potently in its light‐induced cis form. This activity decreased the velocity of Eg5 in single‐molecule assays, promoted formation of monopolar spindles, and led to mitotic arrest in a light dependent way. Abstract : The optical control of a mitotic kinesin, Eg5, was achieved through an azobenzene analog of EMD‐534085. Under UV light conditions, HeLa cells undergo mitotic arrest, as evidenced by the formation of a monopolar spindle.